(untitled) (Third Sector Social Economic Review, 2025)
Purpose – This study aims to determine the contribution of health tourism, which is a sector in the trend of development and growth, to the Turkish economy in the period 2010q1-2023q4. The study attempts to show how promoting medical tourism, as stated in the Health Transformation Program, can increase economic growth in Türkiye. Methodology/Design/Approach – This study analyzes the industrial production index, medical tourism revenues, and real effective exchange rate data to examine the causality relationship in the short, medium, and long term within the framework of the “frequency domain causality approach”. Findings – while there is causality from the industrial production index, which represents economic growth, to medical tourism revenues in every period, no causality was found from medical tourism to economic growth. A causality was found from the real effective exchange rate to economic growth in the short and medium term, but no causality was found f1]Cümle düzeltildi.rom economic growth to the real effective exchange rate. The findings show a causality from medical tourism revenues to the real effective exchange rate in the short term and a causality from the real effective exchange rate to tourism revenues in the medium term. This explains why healthcare services have become cheaper in Turkey due to the increase in the exchange rate. Originality of the research – It is thought that the method and period applied in the study could fill the gap in the literature.